Use of Stent Retriever Thrombectomy Combined With Local Urokinase Thrombolysis for Deep Cerebral Vein Thrombosis: A Case Report - Xu, Qunli; Chen, Yigang; Zheng, Xu; Jin, Xing; Zhang, Jinhua (Frontiers in Stroke, 2022)
Background Deep cerebral vein (DCV) thrombosis is a rare type of cerebrovascular disorder and usually has an unfavorable prognosis. Although endovascular treatment measures for venous sinus thrombosis are well-described and evidenced, relevant reports on DCV thrombosis are presently lacking. Case Report In this report, we present the first case of the successful use of stent retriever thrombectomy combined with local urokinase thrombolysis for DCV thrombosis and have described the detailed procedure. Conclusion The use of stent retriever thrombectomy combined with local thrombolysis was technically feasible and effective for DCV thrombosis. The key to the successful restoration of DCV outflow was to recanalize the occluded vein of Galen.